Detection and Characterization of Salmonella Serotypes in the Production Chain of Two Pig Farms in Buenos Aires Province, Argentina - Colello, Rocío; Ruiz, María J.; Padín, Valeria M.; Rogé, Ariel D.; Leotta, Gerardo; Padola, Nora Lía; Etcheverría, Analía I. (Frontiers in Microbiology, 2018)
The aim of the present study was to determine the prevalence of Salmonella in the pork production chain and to characterize Salmonella isolates. From 764 samples, 35 (4.6%) were positive for Salmonella spp., as determined by biochemical tests and the presence of the invA gene. From these, 2.6, 2.0, 8.8, and 8.0% corresponded to samples collected from farms, slaughterhouses, boning rooms and retail markets, respectively. Salmonella strains were classified into five serotypes and distributed as follows: S. Typhimurium in the pork production chain, S. Kentucky in farms and slaughterhouses, S. Brandenburg in slaughterhouses, S. Livingstone in farms and S. Agona in boning rooms and retail markets. Interestingly, the antimicrobial susceptibility testing indicated that all 35 Salmonella spp.-positive isolates were resistant to at least one antimicrobial agent, and 30 were multidrug-resistant (MDR) and resistant to different classes of antibiotics. The enterobacterial repetitive intergenic consensus-polymerase chain reaction (ERIC-PCR) analysis showed clonal relatedness among strains isolated from farms, boning rooms and retail markets. The presence of antibiotic-resistant Salmonella in food poses a potential health hazard to consumers.